Aplikasi Mulsa Bawah Tanah Pada Budidaya Jagung Manis (Zea mays L. Saccharata) - Nareswari, Aptika; Anindita, Devina Cinantya; Alhaviz, Alhaviz (Universitas Wahid Hasyim, 2024)
Traditional mulching practices primarily involve the surface application of mulch materials. However, underground mulching offers a novel approach to enhance weed control, moisture retention, and nutrient management while optimizing crop yields. This research aims to explore the implementasion of underground mulch in sweet corn cultivation within Kediri Regency, Indonesia from April to July of 2022. We conducted field experiments to evaluate the impact of underground mulch on sweet corn growth compared it to conventional surface mulching with randomized complete block design (RCBD) with three treatments (i) non mulch, (ii) conventional plastic mulch, (iii) underground mulch and four repetitons in cultivationg sweet corn Talenta F1. This research contributes to the advancement of sustainable corn farming practices and provides insight into innovative mulching techniques. Our findings reveal significant advantages of using underground mulch in terms of increasing water availability as observed from the soil moisture content on a scale 1-10, reduce evaporation (Eo), support vegetative growth (plant height), accelerate total chlorophyll level, and increase the ear’s fresh weight.Keywords: crop yields, moisture retention, weed control